Engraving natural justice in the decision making process of the security council - Ahmad, Muhamad Hassan; Ali Mohamed, Ashgar Ali; Masum, Ahmad; Nafees, Seeni Mohamed; Eishan Jan, Mohammad Naqib (IIUM Press, 2022)
The primarily responsibility of the Security Council to maintain international peace and security in accordance with the purposes and principles of the United Nations (UN) on behalf of its Members. All of its decisions are binding on all the UN members and thus it possesses the quasi-executive, quasi-legislative and quasi-judicial power at the international level. Paradoxically, in most cases, its decisions making processes do not really follow the principle of natural justice, i.e., ‘audi alteram partem’ and ‘nemo judex in causa sua’. Thus, it is vital for the Security Council to make its decisions in line with the principles of natural justice. Accordingly, the paper aims at assessing how far the Security Council is in compliance with the principles of natural justice. It is discovered that the Security Council normally invites a party to a dispute to participate in its discussions and this practice is in line with the principle of natural justice, i.e., audi alteram partem. Although Article 27 (3) of the UN Charter requires the Security Council to exclude a party to a dispute to abstain from voting in decisions making relating to Chapter VI and Article 52 (3) of the UN Charter - which is in line with the principle of natural justice, i.e., nemo judex in causa sua - there is no consistency in practice. Hence, authors recommend that a party to a dispute shall abstain from voting in all decisions of the Security Council by virtue of being a party to the dispute regardless of whether it is a permanent or non-permanent member of the Security Council, a member of the UN, or a non-UN member.